Influence of surface condition of copper sheets on ultrasonic metal welding - E. Helfers; F.W. Müller; A. Schiebahn; U. Reisgen (Journal of Advanced Joining Processes, 2024)
Ultrasonic metal welding (USMW) is an industrially widespread joining process. Low heat input and large bonding area qualify USMW for demanding applications such as electrotechnical components. Despite all efforts process and quality fluctuations occur in industrial use. Until now, there is no non-destructive testing method, which makes extensive monitoring of process input variables (work piece characteristics) necessary. USMW is particularly surface-sensitive, but to date no generally valid surface parameters are known for characterizing the weldability of parts and components. Component cleaning before the process is common, but to achieve consistent quality, the cleaning process must be adapted to the condition of the uncleaned component and to the desired surface. In industrial applications, cleaning has so far often been carried out using costly and comparatively environmentally harmful processes based on mechanical and chemical principles. Within this study we investigate prior treatment of copper workpieces for USMW by means of laser beam and compare the results with chemically and mechanically processed samples. Laser treatment of the typically bright copper surfaces (low radiation absorption in the infrared range), remaining organic residues and the new formation of oxide layers pose significant challenges developing a robust process chain. Different laser treatment strategies are compared and evaluated for different initial surface conditions. The influence on the resulting cleaned surface properties, the resulting USMW process and the joint quality thus achieved is experimentally evaluated. An analytical approach to assessing the weldability based on surface properties and surface treatment is derived. The correlation of surface properties of the materials used, the welding process and welding results is possible. The lowest surface roughness and removal of rolling grooves results in the most efficient welding process. The use of laser treatment leads to the desired alignment of different input conditions, which is also represented in the robustness of the welding result. Without adjustment of the welding parameters, the laser treatment used so far results in a reduction of the joint strength.